Perancangan Model Pengukuran Layanan Teknologi Informasi pada Perguruan Tinggi (Studi Kasus: Perguruan Tinggi X) - Adelia Adelia; Kridanto Surendro (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Information technology services within the organization need to be taken to ensure that the service providers can provide quality service and benefit for service user. The research model to measure information technology services provided to users of the service providers, especially in college. In the design of model, using the concepts included in the service intelligence and ISO 20000, Balanced Scorecard, Balanced Scorecard and IT Balanced Scorecard management of information technology services. Measurement services performed by using models generated from mapping the concepts used in the study. Colleges may use the measurement model is a college that has been using information technology in supporting the activities of the college. Measurements of IT service level emphasizes on IT services owned by the college and different type of IT services to users in the college